(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This study examines transparency and accountability in higher education financing through a comparative analysis of Indonesia and Uzbekistan. Using a qualitative documentary approach, the research draws on audited government financial reports, official ministerial accountability documents, and sustainability performance indicators to evaluate financing governance structures and institutional outcomes. The analysis focuses on observable transparency measures, including budget realization discipline, financial reporting standards, audit coverage, and corrective enforcement actions. The findings show that Indonesia demonstrates a reporting-centered accountability model characterized by standardized audited statements and structured disclosure practices, while Uzbekistan reflects an enforcement-centered model with intensive audit controls and corrective financial interventions. Comparative results indicate that stronger reporting transparency and integrated accountability mechanisms are associated with higher institutional sustainability performance and better international ranking positions, as reflected in UI GreenMetric indicators. The study concludes that accountability architecture — rather than funding volume alone — plays a decisive role in translating public financing into measurable institutional performance and global competitiveness in higher education.